1979
DOI: 10.1007/bf02680186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatments on the volatile composition of coconut oil

Abstract: Fresh coconut oil was heated under different conditions for 48 hr at 180 C. The heat treatments included heating in vacuo, heating in air and heating in air and water. The samples were distilled under high vacuum and the volatiles thus obtained were analyzed by combined gas chromatography‐mass spectrometry. In all heated samples, a series of n‐alkanes and I‐alkenes, n‐alkanals, methyl alkanones, alkenals, gamma‐and delta‐lactones, methyl and ethyl esters and free fatty acids were identified. The relative amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…The identification of these peaks was tentatively based on a database of Kovats indices stored in the substance library of the Microsense software using n-alkanes as the standard. Some of the volatile compounds found in this study, such as octane and lactones, were also identified in coconut oil by Pai et al [28] and Jayalekshmy et al [29] and in roasted palm kernels as reported by Jayalekshmy et al [30]. Lactones were the main components giving the characteristic mild, sweet and pleasant coconut flavor [31].…”
Section: Electronic Nose Analysissupporting
confidence: 78%
“…The identification of these peaks was tentatively based on a database of Kovats indices stored in the substance library of the Microsense software using n-alkanes as the standard. Some of the volatile compounds found in this study, such as octane and lactones, were also identified in coconut oil by Pai et al [28] and Jayalekshmy et al [29] and in roasted palm kernels as reported by Jayalekshmy et al [30]. Lactones were the main components giving the characteristic mild, sweet and pleasant coconut flavor [31].…”
Section: Electronic Nose Analysissupporting
confidence: 78%
“…The low mean for the chips fried in RBDCO may be due to the FFA content of the oil. RBDCO produced large amounts of FFA, mostly short and medium chains, which volatilize during frying and produce off-odor (Pai 1980).…”
Section: Sensory Evaluation Of Potato Chipsmentioning
confidence: 99%
“…Some compounds of this nature, as mentioned before, have been previously found in some thermodegraded oils of known or unknown vegetable origin (Takeoka et al, 1996;Chang, Peterson & Ho, 1978;Pai, Lomanno, & Nawar, 1979;Chung, Eiserich & Shibamoto, 1993). In this study the influence of oil type and heating time on the formation of these toxic compounds will be analysed in order to establish if all oils tend to form these toxic compounds in the same way, independently of their composition, or if there are clear differences among them.…”
Section: Introductionmentioning
confidence: 97%